It was her house first - Priest, Cherie (Poisoned Pen Press, 2025)
"Venita Rost, a former silent film star, has stayed put for the last century-fuming and raging, luring investors and ambitious DIYers to their doom in her haunted home on the cliff. But her nemesis also remains: a once-famous detective she blames for the death of her daughter. Inspector Bartholomew Sloan blames himself, too. He couldn't save Priscilla any more than he could save his best friend from the noose. Or save himself from Venita's wrath. Now all he can do is watch as Venita lures each new owner to their death, trapped in this house of horror he helped create and unable to do anything to stop it"--